Gender Earnings Gap in German Firms: The Impact of Firm Characteristics and Institutions - Anja Heinze; Elke Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Most existing analyses on the gender wage gap (GWG) have neglected the establishment as a place where inequality between male and female employees arises and is maintained. The use of linked employee-employer data permits us to move beyond the individual and consider the importance of the workplace to explain gender pay differentials. That is, we first provide a comprehensive study on the effects of various firm characteristics and the institutional framework on the GWG in Germany. The innovation of our research is that we do not just compare average male and female wages (of specific groups of employees), but look at within-firm gender wage differentials. Our results indicate that the mean GWG within firms is smaller than the average overall GWG. Furthermore, we can show that firms with formalized co-determination (works council) and those covered by collective wage agreements are more likely to have smaller GWG. It is also interesting to note that the wage differential between men and women decreases with firm size and increases with the wage level.
Keywords: J16; J31; 330; gender wage gap; unions; works councils; discrimination; within-firms wage differentials; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Geschlechterdiskriminierung; Unternehmen; Arbeitsplatz; Mitbestimmung; Tarifpolitik; Schätzung; Deutschland